HAKIKAT DAN KONSEP PENDIDIKAN TERPADU - Imam Syafi'ie (EL-TARBAWI, 2002)
The following article explores the essence and the integrated education from epistemology point of view, its concept, its curriculum, its object, its goal, its learning process, and the integrated form as an alternative education. According to the writer that the integrated education denotes an alternative education nowadays and in the future. In addition, it is important to formulate the effective form of the integrated system of education should be based on a variety of perspectives. The first step is to formulate the basic of its philosophy, and the next step is how to state the conceptualization of the vision, mission statement, the goal, and afterward the step to decide the effective form so that the system of the integrated education can adapt and response the challenge and the change.